2017
DOI: 10.20517/2394-5079.2016.33
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and free radical-scavenging of cape gooseberry (Physalis peruviana L.) in hepatocellular carcinoma rats model

Abstract: How to cite this article: Hassan HA, Gharib NE, Azhari GF. Antioxidant activity and free radical-scavenging of cape gooseberry (Physalis peruviana L.) in diethylnitrosamine-induced hepatocellular carcinoma. Hepatoma Res 2017;3:27-33.Aim: Oxidative damage of cellular components by free radicals and other reactive oxygen molecules is believed to be associated with the development of degenerative diseases. The aim of the present study was to evaluate the antioxidant capacity and free radical scavenging activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In parallel, Bouaziz-ketata et al 8 have shown that the administration of NaNO 3 caused a remarkable rise of rat liver MDA contents. Owing to the MDA cytotoxicity and inhibitory action on cellular protective enzymes, it is suggested to act as a tumour promoter 45 .…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, Bouaziz-ketata et al 8 have shown that the administration of NaNO 3 caused a remarkable rise of rat liver MDA contents. Owing to the MDA cytotoxicity and inhibitory action on cellular protective enzymes, it is suggested to act as a tumour promoter 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Many human chronic diseases such as cancer, aging, obesity, etc. are believed to be related to the oxidative damage of reactive oxygen species (ROS) to cells ( Hassan, Ghareb & Azhari, 2017 ), the presence of antioxidants (such as total phenol, flavonoids, and SOD) to maintain a dynamic balance between the generation and removal of free radicals in vivo is important. A standard method for assessing the antioxidant capacity of fermented beverages has not been established ( Freire et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the process of cell metabolism, excessive production of free radicals can cause a series of diseases, such as aging, obesity, arteriosclerosis, etc. ( Hassan, Ghareb & Azhari, 2017 ). Therefore, the balance and stability of free radicals is very important for maintaining the body.…”
Section: Introductionmentioning
confidence: 99%
“…59 Moreover, in the diethylnitrosamine and CCl 4 -induced hepatocellular carcinoma rat model, the administration of Cape gooseberry juice led to the improvement of hepatic biomarkers. 60 Regarding the antiproliferative potential of pure isolates, reported that 4β-hydroxywithanolide E obtained from the aerial parts of P. peruviana prevented the growth of colon cancer monolayer and spheroid cultures. At low concentrations, the compound induced cell cycle arrest, and at higher concentrations it induced apoptosis.…”
Section: Papermentioning
confidence: 99%